O quadro de escrever como mediador na relação professor-aluno na aula de matemática - RODRIGUES JÚNIOR, Luiz Feliciano (Universidade Federal do Pará, 2011)
From the consulted bibliographical references about the thematic in exposition, it is produced a thought that leads the reader to the meditation concerning the aspects that influence the cognitive mechanism inherent to the teaching and learning process, directed to the learning of mathematics and the blackboard, that is usufructing directly from the psychology of the mathematical education. The study developed in the mathematical education area has presented some aspects that influence the attitudes of the students with relation to the mathematics in accord to the blackboard. This study aims contribution to the students, teachers or educators about the affectivity that the students present on the subject mathematics; therefore, there are information and suggestion about this relation. The same work brings some anxieties about the use of the blackboard, for example: why the student denies going up to the blackboard when the teacher asks him to? Which are the bigger difficulties? Is it the fear, the insecurity, the lack of learning? At last, it is discussed about the important factors that influence directly the attitude of the student exactly when the teacher uses this tool. Therefore, the objective of this study is to present to the mathematics teachers the importance to reflect about the complex affective relation between the student and the mathematics, and also to the mathematics teacher the knowledge of the most used instrument by the teachers in the classroom (the blackboard). The correct use of the blackboard and what this instrument, when used in a wrong way, can cause to the students. It is believed that, with the possession of this information, many teachers will be leaded to a self?evaluation, to a reflection and a change of attitude in favor of a better education for a better society.